Constructing Scout Identity through Digital Branding: A Qualitative Case Study of Instagram Use in MTA Islamic Boarding School - Lintang Bayu Aji; Sri Hastjarjo; Yulius Slamet (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to analyze the implementation of digital branding strategies conducted by the Scout organization of Pondok Pesantren MTA through Instagram. In the era of digital transformation, social media plays a critical role in constructing institutional identity and image, including within Islamic educational institutions such as pesantren. Using a descriptive qualitative approach, data were collected through in-depth interviews, content observation, and documentation of the Instagram account @pramukaponpesmta. The findings indicate that the account is strategically managed to convey institutional messages, Scouting values, and Islamic educational character consistently. The digital branding strategy includes the use of distinctive visual elements (logos, colors, uniforms), educational narratives in captions, and active interaction with the audience. The content uploaded not only documents activities but also emphasizes character values such as discipline, leadership, and teamwork, which are aligned with the Kulliyatul Mu’allimin Al-Islamiyah (KMI) curriculum. This study concludes that social media can serve as a strategic tool in strengthening pesantren's institutional identity by adapting to the digital sphere. The branding implementation through Pramuka MTA’s Instagram illustrates how Scouting can represent character education values within a modern communication framework.